Haemodynamic assessment during off pump coronary artery bypass grafting in patients with ejection fraction ≥40% and it’s relation to myocardial ischaemia in early postoperative period - Yadav, Surendra Singh; Chakrabarty, Ushnish; Datta, Swernendu; Mukherjee, Plaban (International Journal of Research in Medical Sciences, 2020)
Background: Subtle haemodynamic alterations that happen during manipulation, displacement and mechanical stabilization of the heart in off pump coronary artery bypass grafting (CABG), may be missed if only conventional parameters like Central venous pressure (CVP); Mean arterial pressure (MAP) and Mean pulmonary arterial pressure (MPAP) are being monitored. In this study we have tried to find out if such alterations may be detected by monitoring cardiac output (CO), cardiac index (CI) and stroke volume (SV) in addition to the conventional parameters. Methods: Over a period of one year (February 2014 to January 2015), 40 patients with left ventricular ejection fraction (LVEF) ≥40%, undergoing off-pump CABG were monitored for the above parameters at baseline and while grafting the anterior, lateral and inferior surfaces of heart. Their quantitative Troponin-I values were also measured preoperatively and 24 hours after shifting to intensive therapy unit (ITU) to find out if the subtle haemodynamic compromises were in anyway related to myocardial injury. Results: CO, CI and SV decreased significantly compared to baseline values while grafting anterior, lateral and inferior surfaces of heart in every patient. MAP decreased significantly only while grafting the left circumflex territory. Only 8 patients showed an elevation of troponin-I value postoperatively (p>0.05). Conclusions: We concluded that during Off-pump CABG (OPCABG) there will be subtle alterations in haemodynamic. However, pharmacological interventions, addition of fluids and lowering head end of table based on the changes seen by the new monitoring parameters are more logically guided and becomes more scientific and objective rather than being just arbitrary decisions.